1996
DOI: 10.2337/diab.45.2.205
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and Metabolic Effects of Prophylactic Insulin Therapy in the NOD-scid/scid Adoptive Transfer Model of IDDM

Abstract: Prophylactic insulin therapy prevents IDDM in spontaneous animal models of the disease and has shown promise in preventing the disease in humans. Although large clinical trials have been formed to use this therapy, a comparative analysis of the efficiency of different pharmaceutical forms and doses of insulin in preventing IDDM has not been performed, and the mechanism underlying the observed prevention of disease is unknown. In the NOD-scid/scid adoptive transfer model of IDDM (10(7) new-onset NOD splenocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 2 publications
1
19
1
Order By: Relevance
“…One possibility is a protective effect of insulin, whether by allowing exhausted beta cells to rest or by altering the makeup of the T cells in the pancreas destroying the β cells there. The first reason was the basis for the large North American trial in pre-diabetic people in the late 90's with small doses of parenteral insulin [22]. The second reason was the basis for the large North American trial in pre-diabetic people in the very late 90's with oral insulin [23].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is a protective effect of insulin, whether by allowing exhausted beta cells to rest or by altering the makeup of the T cells in the pancreas destroying the β cells there. The first reason was the basis for the large North American trial in pre-diabetic people in the late 90's with small doses of parenteral insulin [22]. The second reason was the basis for the large North American trial in pre-diabetic people in the very late 90's with oral insulin [23].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, parenteral insulin therapy was reported that it can prevent diabetes in animal models [7,8], and pilot studies have suggested that insulin therapy also delays diabetes in humans [9,10]. In recently, insulin pump is a safe and effective therapy method in treating children and adolescents with T1D [11], and the sensoraugmented pump therapy could improve the glycated hemoglobin level comparing with injection therapy [12].…”
Section: Bioinformatics Analysis Of Gene Expression In Peripheral Blomentioning
confidence: 99%
“…By comparison, the original study in BB rats used 15 U insulin/kg body weight (53). Actually, the very low human dose was later found not to work, either in BB rats or in NOD mice (56). The human dose used might give an immunological effect, which then was not enough for T1D prevention.…”
Section: The Activity Of the Beta Cellsmentioning
confidence: 99%